Sustainable development indicators : much wanted, less used? - Rosenström, Ulla (Finnish Environment Institute, 2013)
For the past twenty years, several indicator sets have been produced on international, national and regional levels. Most of the work has concentrated on the selection of the indicators and on collection of the pertinent data, but less attention has been given to the actual users and their needs. This dissertation focuses on the use of sustainable development indicator sets. The dissertation explores the reasons that have deterred the use of the indicators, discusses the role of sustainable development indicators in a policy-cycle and broadens the view of use by recognising three different types of use.The work presents two indicator development processes: The Finnish national sustainable development indicators and the socio-cultural indicators supporting the measurement of eco-efficiency in the Kymenlaakso Region. The sets are compared by using a framework created in this work to describe indicator process quality. It includes five principles supported by more specific criteria. The principles are high policy relevance, sound indicator quality, efficient participation, effective dissemination and long-term institutionalisation.The framework provided a way to identify the key obstacles for use. The two immediate problems with current indicator sets are that the users are unaware of them and the indicators are often unsuitable to their needs. The reasons for these major flaws are irrelevance of the indicators to the policy needs, technical shortcomings in the context and presentation, failure to engage the users in the development process, non-existent dissemination strategies and lack of institutionalisation to promote and update the indicators. The importance of the different obstacles differs among the users and use types.In addition to the indicator projects, materials used in the dissertation include 38 interviews of high-level policy-makers or civil servants close to them, statistics of the national indicator Internet-page downloads, citations of the national indicator publication, and the media coverage of ...